Understanding Industry Perceptions of the Advertising Agency’s Business Model: Rethinking an Industry that Prides Itself on Thinking Outside the Box - Narsing, Shailini Parbhoo (The IIE, 2020)
According to industry articles (Moteshegwa, 2019; Lee, 2019 and Bianchi 2019), the advertising agency’s model is ‘broken’. This qualitative study’s aim was to understand the perceptions of the ‘broken’ business model and determine whether ad agencies need to adopt disruption or change to their business model practices to be more competitive. This paper sought to understand if the ad agency model is truly ‘broken’ and the factors allowing ad agencies to differentiate themselves and be more competitive in the industry. The research problem was explored through a phenomenological approach and consisted of two sample groups. Semi-structured interviews were conducted and transcribed then data was collected and cross-sectioned through a thematic analysis. The most significant findings was the agreement of the participants, that the ad agency ‘model’ is ‘broken’. In addition, the factors that were criticised were found to not be parts of the model itself. Furthermore, the criticisms did not align with the participants’ recommendations for ad agencies to use in order to fix the supposedly ‘broken’ model. Ultimately, this suggested that both ad agency representatives and their clients were uncertain and that the perception that the standard ad agency model is ‘broken’ is not clearly substantiated.
Keywords: Disruption; Brand differentiation; Client Relationship Model